أهمية التعلم الالكتروني في ضوء المهام الحديثة للتعليم العالي العالمي رؤية مستقبلية عن حالة الجزائر. - بخوش, الدكتور: وليد (Sciences de l'Homme et de la Société, 2015)
يحاول الباحث في هذه الورقة البحثية أن يقدم رؤية مستقبلية عن مكانة التعلم الالكتروني في الجزائر من منظور تدويل التعليم العالي وما أنتجه هذا المفهوم من تحولات في مهام ورسالة التعليم العالي عالميًا، وذلك بتقديم عرض عن ماهية التعلم الالكتروني، ثم عرض أهم المهام الحديثة للتعليم العالي العالمي، وصولاً إلى إبراز حاجة منظومة التعليم العالي في الجزائر إلى مثل هذا النوع من التعليم، ضمانًا لمواكبة التطورات العلمية والمعرفية الحديثة. Abstract : We attempt, in the present paper, to present a prospective view about the position of the e-learning in Algeria in relation to the internationalization of higher education; a notion that made many changes concerning tasks and missions of higher teaching. First, we present an exposé about the nature of higher education, and then we enumerate the main modern tasks of higher education to show, at the end, how much the system of higher education in Algeria needs such a kind of learning in order to go with new developments in the field of science and knowledge.